Human rights for children with disabilities in Malaysia: issues and challenges - Md. Tah, Ikmal Hisham; Mokhtar, Khairil Azmin (The Faculty of Law, Universiti Teknologi MARA (UiTM), 2016)
Children with disabilities require protection of their rights from the society. They are disabled because society excluded, discriminated and encouraging negative stigma against them. The UN Convention on the Rights of Persons with Disabilities (CRPD) especially Article 7 has mentioned that the State Parties shall promote and protect the rights of children with disabilities including providing necessary measures on an equal basis with others. The concept of the best interest of child has become a primary consideration, together, with expressing their views freely in accordance with their age and maturity has been embodied within the convention. Malaysia has ratified the said Convention in 2010 and enacting Persons with Disabilities (PWD) Act 2008 to fulfil their international obligations. Furthermore, the new Education (Regulation) Special Education 2015 has been gazetted to show government’s commitment to upholding their rights in all aspects of life. However, various issues and challenges being faced to ensure the human rights approach in accordance with the CRPD being implemented, to improve the condition of children with disabilities. This article will elaborate the Malaysian commitment to improving the life of children with disabilities in accordance with human rights approach towards disabilities. It would assist the agenda to recognize their full potential to live fullest which will be important and significant for developing nation like Malaysia. The final analysis showed that there is the need for full cooperation between government, private sectors, non-governmental and disabled people organisations to promote and protect the rights of children with disabilities in all aspects of life.